4x - 12x5
In this case, this is an expression in terms of x. The only way it could be simplified would be to factor out the 4x to get
4x(1-3x4)
OR, you could have meant the following:
4 x (-12) x 5
= -20 x 12
= -240
12x-17x = -5
12x + 5 - 2x =(12x - 2x) + 5 =10x + 5 =5 (2x + 1)
When x = 5, 12x = 12*5 = 60.
x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0
4x2 + 12x + 5 = (2x + 1)(2x + 5).
12x-17x = -5
-9x 2 -12x+5 =
12x + 5 - 2x =(12x - 2x) + 5 =10x + 5 =5 (2x + 1)
5/4x+7/12x is the same as 15/12x+7/12x = 21/12x
When x = 5, 12x = 12*5 = 60.
x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0
4x2 + 12x + 5 = (2x + 1)(2x + 5).
12x = 11x - 5, subtract both sides by 11x x = -5
17
-5 + 12x = 18x + 7Subtract 7 from each side:-12 + 12x = 18xSubtract 12x from each side:-12 = 6xDivide each side by 6:-2 = x
After collecting like terms, (3 - 5x - 5 - 12x) reduces to (-2 - 17x).
12x^3+17x^2+5x=0x(12x^2+17x+5)=0x(x+1)(12x+5)=0x=0x=-1x=-5/12